Meditation in the Workplace: Does Mindfulness Reduce Bias and Increase Organisational Citizenship Behaviours? - Williams, Emma Constance; Polito, Vince (Frontiers in Psychology, 2022)
Mindfulness is becoming increasingly popular in the workplace. This likely relates to a growing body of research linking mindfulness to a range of psychological outcomes such as reduced anxiety, depression and increased subjective wellbeing. However, whilst mindfulness has received a great deal of attention in clinical research, the evidence for workplace relevant benefits is less established. Additionally, outside of clinical research, mindfulness studies have rarely been replicated. Recent evidence suggests that the cognitive skills cultivated during meditation may be instrumental in reducing biased thinking and increasing prosocial behaviour, but these findings have not been previously tested in a workplace setting. Specifically, mindfulness has been linked to reductions in implicit age bias, sunk-cost decision-making bias and increases in organisational citizenship behaviours. In two experiments using a workplace and laboratory sample, the present investigation aimed to test the reliability and generalisability of previous findings that a brief mindfulness meditation can reduce age and sunk-cost decision-making biases. To more directly test the potential positive benefits of mindfulness in a workplace setting, this study also investigated the impact of a mindfulness intervention on intention to perform organisational citizenship behaviours (OCB). Whilst meditation significantly increased OCB intent, predictions relating to bias were not supported. Considerations for the degree to which empirical evidence aligns with claims in popular culture, along with implications for the practical uses of mindfulness in the workplace are explored.